Novel Antitumor Platinum(II) Conjugates Containing the Nonsteroidal Anti-inflammatory Agent Diclofenac: Synthesis and Dual Mechanisms of Antiproliferative Effects - Intini, Francesco Paolo; Zajac, Juraj; Novohradsky, Vojtech; Saltarella, Teresa; Pacifico, Concetta; Brabec, Viktor; Natile, Giovanni; Kasparkova, Jana (Inorganic chemistry, 2017)
One concept how to improve anticancer effects of conventional metallodrugs consists in conjugation of these compounds with other biologically (antitumor) active agents, acting by a different mechanism. Here, we present synthesis, biological effects, and mechanisms of action of new Pt(II) derivatives containing one or two nonsteroidal anti-inflammatory diclofenac (DCF) ligands also known for their antitumor effects. The antiproliferative properties of these metallic conjugates show that these compounds are potent and cancer cell selective cytotoxic agents exhibiting activity in cisplatin resistant and the COX-2 positive tumor cell lines. One of these compounds, compound 3, in which DCF molecules are coordinated to Pt(II) through their carboxylic group, is more potent than parental conventional Pt(II) drug cisplatin, free DCF and the congeners of 3 in which DCF ligands are conjugated to Pt(II) via a diamine. The potency of 3 is due to several factors including enhanced internalization that correlates with enhanced DNA binding and cytotoxicity. Mechanistic studies show that 3 combines multiple effects. After its accumulation in cells, it releases Pt(II) drug capable of binding/damaging DNA and DCF ligands, which affect distribution of cells in individual phases of the cell cycle, inhibit glycolysis and lactate transport, collapse mitochondrial membrane potential, and suppress the cellular properties characteristic of metastatic progression.
Keywords: protinádorové látky; Cell Line, Tumor; Cell Proliferation; Structure-Activity Relationship; Drug Screening Assays, Antitumor; molekulární struktura; Molecular Structure; Diclofenac; vztah mezi dávkou a účinkem léčiva; Organoplatinum Compounds; vztahy mezi strukturou a aktivitou; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; lidé; Humans; diklofenak; proliferace buněk; screeningové testy protinádorových léčiv; nádorové buněčné linie; organoplatinové sloučeniny; Dose-Response Relationship, Drug; Antineoplastic Agents